Smoking habits and parathyroid hormone concentrations in young adults: The CARDIA study - Akira Fujiyoshi; Lynda E. Polgreen; Myron D. Gross; Jared P. Reis; Stephen Sidney; David R. Jacobs, Jr. (Bone Reports, 2016)
Conflicting results have been reported concerning a relationship between smoking and serum PTH. Our study objective was to examine whether smoking was associated with serum PTH independent of correlates of PTH among young adults, and explore potential mechanisms.This was a cross-sectional study of healthy individuals, 24–36 years old, examined during 1992 through 1993 in California, USA (a subset of Coronary Artery Risk Development in Young Adults study).Linear regression was used to obtain adjusted means of PTH according to smoking habit (current, former, never). Biomarkers for calcium metabolism and bone turnover (including serum concentrations of osteocalcin, bone-specific alkaline phosphatase, and 24-hour urinary excretion of calcium) and bone mineral density were similarly compared by smoking.376 participants were analyzed (171 women, 181 black). Over half reported never smoking. We observed lower PTH in current smokers compared to non-smokers and found no evidence of an interaction by race and sex. PTH was lowest in current smokers, intermediate in former smokers, and highest in never smokers (geometric mean PTH: 23.6, 26.7, 27.4 pg/mL, respectively: P for trend, 0.006) after adjusting for potential confounders including calcium intake. Among the biomarkers, serum osteocalcin concentration and 24-hour urinary excretion of calcium were lowest in current smokers. We observed no smoking-related difference in bone mineral density.In this community-based sample of young adult men and women, smoking was associated with significantly lower PTH concentration. The mechanism and clinical implication of the finding, however, remains uncertain. Keywords: Parathyroid hormone, Smoking, Young adults